Regional identities and competitiveness in a globalised environment: New challenges for Greek regions. - Anastasia Nikoli; Fotini Zigouri (European Regional Science Association (ERSA), 2011)
Over the last decades, at a European level, efforts have been made so that regions become capable of sustainable economic growth, with great social cohesion and better distribution of wealth, while at the same time under open market conditions, they are being exposed to external competitiveness. In order to survive and gain advantage from globalised economies, regions have to (re)form and promote a competitive profile that differentiates them from other regions and promises potentials of further development. At that point, a competitive `identity' could be a key factor in dealing with persistence and change, in today's globalised environment. The formation of regional identities seems to be a matter of great concern amongst decision / policy makers. Space in general, has a symbolic and ideological dimension, as well as a material basis that reflect the stage of development in societies. Regional identities which have a strong collective dimension, are related to factors that define and constitute societies (history, collective memory, governance, economy, culture, etc), reflect a certain inner or/and outer image and seem to be a mean to understand and measure regional development. At a social level, identities satisfy the need of belongingness and of sharing common goals, beliefs and values. Thus, they play a privileged role in strengthening social and economic cohesion by fortifying the collective consciousness and provoking the driving forces of development, especially when regions face challenges. In Greece, the recent administrative reorganizational program established by a new law in 2010, incorporates new multidimensional criteria for regional planning and development and offers potential for formation of competitive regional identities. By merging into greater ones, Greek regions could gain the required resources to face the challenges created by the economic crisis and by the high competitive and globalised environment. The new law underlines the need to restructure the economy and the regional governance system and reinforces public participation in decision making and planning process. These changes could raise the interest in forming attractive identities which, into the future and along with new regional planning strategies, could provide opportunities for economic growth and prosperity to Greek regions.
Keywords: 330